The Effect of Surface Characteristics on Contact Line Motion in Immersion Lithography - Burnett, Holly B. (University of Wisconsin-Madison, 2005)
Optical lithography has been the technology of choice in the semiconductor industry for decades. As the industry progresses, new methods are sought to manufacture smaller and faster integrated circuits. One possible next-generation lithography technology is immersion lithography. In immersion lithography, the air gap that currently exists between the last lens element of the exposure system and the wafer is filled with a liquid that more closely matches the refractive index of the lens. There is a possibility that air bubbles, which represent a refractive index discontinuity, may be present in the liquid within the active exposure region and cause imaging errors. One potential source of bubble generation is related to the flow of liquid over previously patterned features, or topography, during scanning or filling. Another potential source of bubbles is related to droplets being deposited on the wafer surface. These droplets can re-encounter the meniscus, entraining air upon impact. Droplets can be deposited on the wafer surface by thin film pulling or meniscus overflow. Film pulling occurs when the receding dynamic contact angle approaches 0? so that a thin film of liquid is pulled out of the meniscus. Meniscus overflow occurs when the immersion fluid does not remain contained in the gap, and instead advances with the wafer. The contact angle is a critical parameter that governs the behavior of the contact line and therefore the entrainment of air and the deposition of droplets on the wafer surface. A hydrophobic surface is more likely to trap air than on a hydrophilic one. The contact angle can be a strong function of the flow velocity; a hydrophilic surface can exhibit hydrophobic behavior when the velocity of the free surface becomes large. Therefore, the contact angle was experimentally measured under static and dynamic conditions for a number of different surfaces, including resist-coated wafers. Contact angle hysteresis quantifies the degree of surface heterogeneity, and was also measured on these test surfaces. The flow of liquid across surface topography was examined using both experimental vi- sualization and CFD modeling. No air entrainment was observed or predicted over the velocity and contact angle conditions that are relevant to immersion lithography. However, experiments and CFD modeling examining droplet-meniscus impact both show that air en- trainment by this mechanism is possible for immersion lithography conditions. Receding meniscus behavior was also investigated; film pulling and meniscus overflow were observed in immersion lithography conditions. An engineering model was developed to approximately predict the critical substrate velocity leading to meniscus overflow. This model can be applied to immersion lithography system design to help avoid this behavior.
Under the supervision of Professor Timothy A. Shedd; 102pp.
Keywords: Thesis (M.S.)--University of Wisconsin--Madison, 2005.; Dissertations Academic Mechanical Engineering.; University of Wisconsin--Madison. College of Engineering.